Key factors in determining surgical timing of total knee arthroplasty in osteoarthritic patients: age, radiographic severity, and symptomatic severity - Chang, Chong Bum (Springer Milan, 2010)
BACKGROUND: Patient age, radiographic severity of osteoarthritis (OA), and severity of symptoms are typically considered as the three key factors in selecting the osteoarthritic patients for total knee arthroplasty (TKA). The purpose of this study was to evaluate the associations between the three selection criteria and the postoperative outcomes including patient satisfaction. We also attempted to determine whether the patients not fully satisfying the criteria are different from the typical candidates in postoperative outcomes. MATERIALS AND METHODS: Three hundred and eighty-three uncomplicated TKAs with 1-year follow-up data were included in this study. We evaluated three preoperative factors including age, radiographic severity of OA, and WOMAC pain and function scores as proxies of preoperative level of symptoms. Evaluation of the postoperative outcomes included WOMAC pain and function scores and the level of patient satisfaction. Regression analyses were used to investigate the associations between the preoperative factors and the postoperative outcomes. Comparative analyses of the postoperative outcomes were made between the typical candidates with all selection criteria and the groups of patients who did not meet one of the selection criteria. RESULTS: Increasing age was associated with worse postoperative functional outcomes. Worse preoperative WOMAC pain and function scores were associated with worse postoperative WOMAC pain and function scores, and had a statistical tendency toward higher patient dissatisfaction. Compared to the typical candidates, the groups of patients who did not meet one of the selection criteria did not have worse postoperative outcomes. On the contrary, the group of younger age and the group with less severe preoperative symptoms were more likely to have better postoperative outcomes. The radiographic severity of OA had no significant associations with any of postoperative outcomes. CONCLUSION: This study indicates that, when considering TKA as a treatment option, orthopedic surgeons need to comprehend the selection criteria in an overall view to offer the best timing for optimal postoperative outcomes.